Ponseti technique: efficacy in idiopathic clubfoot in Indian population - Mahajan, Neetin; Ramteke, Ujwal; Gavhale, Sandeep; Palange, Nikhil; Mane, Akash; Dave, Harshit (International Journal of Research in Orthopaedics, 2018)
Background: The number of operations for clubfoot is many, but the results are not encouraging and more complications are encountered after operative treatment. Most surgeons believe manipulation to be easy; however they rarely complete the treatment and abandon it and go on to surgery. In the confusing scenario Ponseti Method evolved and proved across the world to be one of the most promising ways to correct club foot with low cost minimum surgery and good result in short period of time. Methods: 50 cases of idiopathic clubfeet (76 feet) were enrolled from a period of May 2006 to May 2008 in the department of Orthopaedic. Out of 50, 42 patients were followed-up for two years. Post tenotomy follow-up done every monthly for 3 months. At every visit babies were checked for any relapse and parents were counselled for the strict compliance with Foot Abduction Brace. The results of correction in 42 patients (64 feets) evaluated and compared with Ponseti's observation and other form of conservative management. Results: The analysis of results of correction of clubfeet deformity by Ponseti's method reveals around 95.30% of good to acceptable result as compared with Ponseti’s observation of around 99% which is comparable. We have observed 4.69% of poor result as compared with 1% observed by Ponseti. Conclusions: It is safe, efficient, Economical and most effective treatment for clubfoot which decreases the need for extensive corrective surgery. This technique can be used in children up to one year of age even after previous unsuccessful non-surgical treatment.